Three New Compounds from Aspergillus terreus PT06-2 Grown in a High Salt Medium - Weiming Zhu; Peipei Liu; Wei Wang; Yi Wang; Jinkai Zheng (Marine Drugs, 2011)
To investigate the structurally novel and bioactive natural compounds from marine-derived microorganisms under high salinity, the fungus Aspergillus terreus PT06-2 was isolated from the sediment of the Putian Sea Saltern, Fujian, China. Three new compounds, terremides A (1) and B (2) and terrelactone A (3), along with twelve known compounds (4–15) were isolated and identified from the fermentation broth of A. terreus PT06-2 at 10% salinity. Among these metabolites, compounds 4 and 15 only produced in the 10% salinity culture, were identified as methyl 3,4,5-trimethoxy-2-(2-(nicotinamido) benzamido) benzoate, and (+)-terrein, respectively. The new compounds 1 and 2 exhibited antibacterial activity against Pseudomonas aeruginosa and Enterobacter aerogenes with MIC values of 63.9 and 33.5 μM, respectively. Compounds 5 showed moderate anti-H1N1 activity and lower cytotoxicity with IC50 and CC50 values of and 143.1 and 976.4 μM, respectively.